Prevalence and associated harm of engagement in self-asphyxial behaviours ('choking game') in young people: a systematic review. Issue 12 (25th June 2015) - Busse, H; Harrop, T; Gunnell, D; Kipping, R
Abstract : Objective: To assess the prevalence of engagement in self-asphyxial (risk-taking) behaviour (SAB) ('choking game') and associated morbidity and mortality in children and young people up to age 20. Design: Systematic literature review. Search strategy: Electronic database search of MEDLINE, Embase, PsycINFO, CINAHL, PubMed, Web of Science Core Collection, BIOSIS citation index and the Cochrane register with no language or date limits applied. References of key papers were reviewed, and experts were contacted to identify additional relevant papers. Eligibility criteria: Systematic reviews, cross-sectional, cohort and case–control studies, and case reports examining SAB with regard to individuals aged 0–20 years, without explicitly stated autoerotic, suicidal or self-harm intentions were included. Results: Thirty-six relevant studies were identified, and SAB was reported in 10 countries. In North America, France and Colombia, awareness of SAB ranged from 36% to 91% across studies/settings, and the median lifetime prevalence of engagement in SAB was 7.4%. Six studies identified the potential for SAB to be associated with engagement in other risk behaviours. Ninety-nine fatal cases were reported. Of the 24 cases described in detail, most occurred when individuals engaged in SAB alone and used a ligature. Conclusions: The current evidence on SAB among young people is limited, and stems predominantly from North America and France. Awareness of SAB among young people is high, and engagement varies by setting. Further research is needed to understand the level of risk and harm associated with SAB, and to determine the appropriate public health response.